2021
DOI: 10.1177/10738584211037619
|View full text |Cite
|
Sign up to set email alerts
|

Visual Plasticity in Adulthood: Perspectives from Hebbian and Homeostatic Plasticity

Abstract: The visual system retains profound plastic potential in adulthood. In the current review, we summarize the evidence of preserved plasticity in the adult visual system during visual perceptual learning as well as both monocular and binocular visual deprivation. In each condition, we discuss how such evidence reflects two major cellular mechanisms of plasticity: Hebbian and homeostatic processes. We focus on how these two mechanisms work together to shape plasticity in the visual system. In addition, we discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 194 publications
0
4
0
Order By: Relevance
“…Prior tDCS studies have investigated various types of visual cortex plasticity, including Hebbian plasticity (e.g., perceptual learning) and homeostatic plasticity (e.g., ocular dominance plasticity). The distinct mechanisms underlying these different types of plasticity 32 may explain why tDCS had effects on some types of plasticity but not on ocular dominance plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Prior tDCS studies have investigated various types of visual cortex plasticity, including Hebbian plasticity (e.g., perceptual learning) and homeostatic plasticity (e.g., ocular dominance plasticity). The distinct mechanisms underlying these different types of plasticity 32 may explain why tDCS had effects on some types of plasticity but not on ocular dominance plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…One suggested mechanism for monocular deprivation is homeostatic plasticity ( Baroncelli and Lunghi, 2021 ; Bang et al, 2023 ), an inherent mechanism that maintains the normal functioning of the neural system by stabilizing neuronal activity ( Keck et al, 2017 ). To accomplish this, the mechanism resets the neural system to its baseline state following a perturbation, preventing the system from becoming hyperactive or hypoactive ( Turrigiano, 1999 ; Turrigiano, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, short-term monocular deprivation and its underlying Wang et al 10.3389/fpsyg.2023.1282113 Frontiers in Psychology 02 frontiersin.org mechanisms have been extensively investigated (Lunghi et al, 2015;Bai et al, 2017;Kim et al, 2017;Min et al, 2019;Lyu et al, 2020;Nguyen et al, 2021). One suggested mechanism for monocular deprivation is homeostatic plasticity (Baroncelli and Lunghi, 2021;Bang et al, 2023), an inherent mechanism that maintains the normal functioning of the neural system by stabilizing neuronal activity (Keck et al, 2017). To accomplish this, the mechanism resets the neural system to its baseline state following a perturbation, preventing the system from becoming hyperactive or hypoactive (Turrigiano, 1999;Turrigiano, 2011).…”
Section: Introductionmentioning
confidence: 99%
“… 7 In PL based on the lateral masking paradigm, the stimuli include a series of Gabor patches with two flanking Gabors, which have been shown to enhance the stimulation and activation of receptive fields in the visual cortex and induce improvement in visual function by facilitating neuronal connections at the cortical level. 8 Polat et al (1994) first reported that the lateral masking paradigm could improve visual function in adult patients with amblyopia, including visual acuity and contrast sensitivity; since then, this training paradigm has also been applied in the treatment of different types of amblyopia as well as other eye diseases, such as myopia, macular degeneration, and glaucoma. 9 12 In Polat's study, after training, the subjects' cortical spatial range of lateral interactions increased by a factor of six.…”
Section: Introductionmentioning
confidence: 99%